Orientating disability studies to disablist austerity: applying Fraser's insights. Issue 2 (7th February 2016) - Dodd, Steven
Abstract: Many disabled people in Britain have experienced profound challenges brought about by a government policy programme characterised by 'austerity'. Drawing on the work of Fraser and Polanyi, this article explores new ways in which disability studies can become theoretically orientated to the task of explaining and challenging what has become an issue of overbearing importance for many disabled people. It is argued that Fraser's notion of bivalency encapsulates the combination of cultural and economic challenges which characterise 'disablist austerity'. Fraser's development of Polanyi's work is used to argue that disability studies should be orientated to large-scale economic challenges as well as cultural and discursive concerns that are more often the object of study in the field.